Extracellular vesicles from medicated plasma of Buyang Huanwu decoction-preconditioned neural stem cells accelerate neurological recovery following ischemic stroke - Long, Jun; Gu, Chenyang; Zhang, Qiankun; Liu, Jiale; Huang, Jiajun; Li, Yajing; Zhang, Yifan; Li, Rong; Ahmed, Waqas; Zhang, Jianfeng; Khan, Ahsan Ali; Cai, Hengsen; et al. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The neurological impairment of survivors after ischemic stroke poses a serious risk to their quality of life and health. Effective therapeutic options are still lacking. Neural stem cells (NSCs) promote neurogenesis via secreted extracellular vesicles (NSC-EVs), which would be a potential therapeutic option, but the insufficient quantity of NSC-EVs in vivo restrains clinical application. Buyang Huanwu Decoction (BHD), a classic traditional Chinese medicine (TCM) decoction, is promising to alleviate neurological impairment after ischemic stroke. It was speculated that BHD might promote neurological recovery through the NSC-EVs. Methods: The medicated plasma of BHD (MP-BHD) was prepared to precondition NSCs and isolate EVs (BHD-NSC-EVs). Middle cerebral artery occlusion (MCAO) models and primary NSCs were administered to evaluate the therapeutic effect. Next-generation sequencing was performed to explore the mechanism. Results: The BHD-NSC-EVs more significantly accelerated neurological recovery after MCAO and promoted NSCs proliferation and differentiation than BHD and NSC-EVs alone. MP-BHD enhanced the largescale generation of BHD-NSC-EVs, which encapsulated functional miRNA and may play critical roles in neurogenesis. Discussion: In replacing BHD or NSCs, the preconditioned NSC-EVs present a more efficient therapeutic strategy for ischemic stroke. Based on the clinical efficacy of TCM, the preconditioning of NSC-derived EVs via the MP of TCM herbs would presents a newly promising therapeutic strategy for neurological diseases.